34 MYRE: An e-learning system for radiotherapy. (December 2018) - Lavielle, J.B.; Carles, F.; Milhas, L.; Daguenel, P.; Simon, L.
Abstract : Introduction: The size of Radiotherapy (RT) departments makes difficult to organize a complete in-house training for the therapists. In a French center there are often 40 to 50 therapists and treatment time slots are large so it is difficult to achieve a classic training. Moreover the training is mainly achieved by people who are poorly available (physicists, physicians, therapists …). Nevertheless the needs of training are very important. Indeed, RT therapists have a central role in the patient security chain and technologies evolve very quickly. New skills and knowledge are continuously asked (new devices, new treatment techniques or a simple software or hardware update). We present in this work the MYRE (MY Recordable E-Learning) database developed in our cancer center that is a full solution of e-learning of RT therapists. Methods: A Microsoft ACCESS database (BDD) was implemented. It contains all the information concerning the therapists and a link to approximately 200 micro-modules. It allows recording and requesting every training act (request can be done for a given therapist, a given module, a year…). These 200 micro-modules are separated in three types: 1. Simple written procedures from the institutional document database that the user must read. 2. Some particular techniques that the user must see. 3. SPOC (Small Private Online Classes): these videos that we made last generally 10 min and are associated to an online multiple-choice test (MCT). This MCT are auto-corrected: the user obtains a score and explanations are given to understand the correct answers. The therapists can access to MYRE in complete autonomy (training, evaluation, and recording of the acquired micro-modules). Results: Between January and March 2018, approximately 600 training acts were recorded in MYRE. Special requests were implemented to allow the manager to edit some specific lists like "list of therapists with all the mandatory skills for a given medical device". Some therapists are involved in the database maintenance and the making of videos and MCT. Conclusion: A database with a link to 200 documents (videos or written procedures) was developed and deployed in the department. It allows the therapists to train in full autonomy. In this study we made a lot of videos and observed that they are an effective tool to introduce technical concepts while written procedures are better for the description of tasks. MYRE is well accepted by therapists (results of an internal audit).